PERAN ROHANI ISLAM (ROHIS) TERHADAP SIKAP RELIGIUSITAS SISWA (Studi Kasus di SMA Negeri 20 Jakarta Pusat) - Wahyu Abdul Hakim; Nurhikmah; Faris Hissi; Fauzan Hamdi; Yayah, Husheini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is a conscious and planned effort to create a conducive learning environment so that students can actively develop their abilities and potential. One important aspect in shaping a person's character is the level of faith, and religiosity is reflected not only in the performance of worship but also in a person's spiritual experience and in how religious values are applied in daily social life. Although SMAN 20 Jakarta Pusat has established the Rohani Islam (ROHIS) organization as a forum for religious guidance, there has been no specific study analyzing the role of ROHIS in influencing students' religious attitudes from three main aspects, namely the practice, experience, and consequence dimensions. This study applied a qualitative approach with a descriptive method designed in the form of a case study. Data were collected through observation, interviews, and documentation involving seven informants, namely the ROHIS advisor, the ROHIS chairperson, four active ROHIS members, and an Islamic Education teacher, and were analyzed using the Miles, Huberman, and Saldana model consisting of data collection, data condensation, data display, and conclusion drawing and verification. The results show that ROHIS plays an important role in improving students' religiosity at SMA Negeri 20 Jakarta Pusat through guidance in the practice, experience, and consequence dimensions. These three dimensions developed in an integrated manner through sustainable ROHIS programs, supported by the exemplary conduct of advisors and administrators as well as the active involvement of all members.